Physical and mechanical properties of thermosensitive xanthan/collagen-inspired protein composite hydrogels. Issue 3 (11th February 2016) - Pham, Thao T. H.; Snijkers, Frank; Storm, Ingeborg M.; de Wolf, Frits A.; Cohen Stuart, Martien A.; van der Gucht, Jasper
ABSTRACT: Functionalization of xanthan hydrogels is of interest for biomaterial applications. The authors report characterization of electrostatic complexation of xanthan with a recombinant collagen-inspired triblock protein polymer. This polymer has one charged polylysine end-block that can bind to xanthan by electrostatic interactions, and another end-block that can self-assemble into thermosensitive collagen-like triple helices; the end-blocks are connected by a neutral, hydrophilic, mostly inert random coil. The protein modifies the xanthan/protein composite hydrogels in three ways: (a) a significant increase in storage modulus, (b) thermosensitivity, and (c) a two-step strain softening in nonlinear rheology. GRAPHICAL ABSTRACT: